Water supply in Ndirande : a case study of a peri-urban community in Blantyre, Malaw - McVeigh, Nina (Cranfield University, 2012)
Access to water and sanitation can lift people out of poverty by improving health and releasing resources to engage in income generating activity. The purpose of this study is to investigate the current water supply situation in the peri-urban community of Ndirande in Blantyre, Malawi and make recommendations for action by a small NGO. Within the specific context of water supply in Blantyre, the research aimed to identify key stakeholders both in the profit and non-profit sector, understand demand by discovering what water sources were being used and what for and finally to identify feasible water supply solutions. The research strategy is that of a case study to gain an understanding of the complex water and sanitation issues facing the people of Ndirande and assist in developing a strategy of water intervention that has both impact and sustainability. The study carried out a transect walk, 4 semi-structured interviews with stakeholders, surveyed 48 households and conducted 12 Water Source Assessment & Sanitation surveys. It was found that 85% of those surveyed had access to water kiosks though unimproved water sources were still in use. Both sources have a high risk of contamination due to poor sanitation, drainage and animal waste. Most water is sourced from Blantyre Water Board (BWB), however the current infrastructure is struggling to keep up with demand and there are periods where water is not available. The community has developed a number of coping strategies to manage periods without water and perceived poorer water quality. BWB faces growing pressures from a growing population, demands to increase coverage, increasing consumption associated with rising living standards and water losses. Under this scenario, water scarcity is likely to increase and areas increasingly affected by water rationing and disrupted supply. Key recommendations of this study are that further support is provided for water storage at both the community and household level and for water treatment at the point of consumption.
Keywords: Water utility; demand; coverage; water usage; coping strategy